Confiança e risco em decisões estratégicas: uma análise a partir de elementos do sistema experiencial - Passuello, Caroline Benevenuti (Universidade do Vale do Rio do Sinos)
This study discusses relations between decision making, risk and trust. Decisions can be studied by experiential system, which is quick, generally automatic, not conscientiously perceived, and involves subjective elements in decision processes. This research is streamed aside the experiential view analysis, aiming to analyze how experiential system elements interfere in necessary trust setting, that allows risk taking in strategic changes decision processes. Four brazilian organizations that passed through strategic changes are studied, based on a qualitative perspective. Data were collected from semi-structured questionnaires, applied to senior executives in in-depth interviews. Interviews contents were analyzed, and the outcomes pointed out the influence of experiential system elements in strategic changes decision processes. It emerges that those elements do not impact in reality, changing risk or uncertainty conditions of the situations that executives are passing through, but they interfere in executives
Keywords: confiança; risco; sistema experiencial; tomada de decisão; mudança organizacional; decision making; experiential system; risk; trust; organizational change; Ciências Sociais Aplicadas